Evaluation of dengue virus seroprevalence in four boroughs of Mexico City among persons aged 5-35 years in 2022 - Eleazar Coba-Alcalá; Lilia Chihu-Amparán; Irma Yvonne Amaya-Larios; Susana Román-Pérez; Rene Santos-Luna; Lorena Suárez-Idueta; Sonia López-Álvarez; Cristal Morales-Trevizo; Jesús Felipe González-Roldán; Ruth Aralí Martínez-Vega; José Ramos-Castañeda (Journal of Infection in Developing Countries)
Introduction: Dengue is currently the most widespread vector-borne disease, and its transmission has been intensively studied in endemic/hyperendemic localities. However, to obtain a complete picture of dengue transmission, it is necessary to study nonendemic localities. Imported dengue cases have been reported in Mexico City, and the presence of eggs of the vector Aedes aegypti has been detected.